Methodology of Parameters Estimation of Flows of Extremal Situations of Telecommunication Network for the Problems of Optimal Distribution of Protection Resources - Виноградов, Н. А.; Коробко, В. В.; Задоя, Г. М.; Скоропаденко, А. П.; Вовк, В. М. (Problems of Informatization and Control, 2004)
The problem of protection from threats for telecommunication networks is learned. Methodology of canonical series expansion of probability distribution of threats flow is developed. The results implement for calculation of time intervals of constant threats flow for corresponding assignment of protection resources